Application of the SAS Method in Beginning Reading Learning in the 21st Century - Francisca Lisa Andriyani; Hermanto Hermanto (Universitas Pendidikan Ganesha, 2022)
Many teachers still experience problems in teaching early reading using the SAS method in the 21st Century. This problem is exacerbated by the sudden change in the teaching system due to the Covid19 Pandemic, which affects the implementation of boldly carried out learning. Therefore, this study aims to analyze whether teachers have applied the SAS method in early reading learning in the 21st Century during bold learning or not. This type of research is survey research with a quantitative descriptive approach. The number of samples was 64 parents of students who were randomly selected using the probability sampling technique of simple random sampling type. Sampling in the study was calculated using the minimum sample table according to Krejcie and Morgan. The instruments used include questionnaires, observations, and interviews. The research data shows an increase in each initial learning meeting using the SAS method in the 21st Century during bold learning. It is proven by the results obtained in the first meeting, which were very good, the second meeting was very good, the meeting was very good, and the meeting was very good. In addition, the data on the spread of distribution shows that all parents say that the average tendency of teachers to apply the SAS method in the 21st Century in learning is in the good brave category.